Punch graft on stable vitiligo patient with HIV - Prabandari, Diah Pitaloka; Novianto, Endi; Wiraputranto, Maria Clarissa; Fitri, Eyleny Meisyah; Kamila, Noer (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Vitiligo is an autoimmune disease caused by melanocyte destruction, with clinical manifestations of milky white depigmented macules and firm borders. This disease can occur at any age, has multifactorial predisposing factors and one of them is viral infection. In recent years there have been numbers of case report showing a correlation between HIV infection and vitiligo. We present a 42-year-old man with HIV positive and vitiligo since 2008. Lesions initially appeared on the stomach and then spread throughout the body and face. Patients received anti-retroviral (ARV) therapy from the beginning of HIV diagnosis and received vitiligo treatment, which is a combination of topical steroid and whole body narrowband Ultraviolet B (nb-UVB) phototherapy for the last three years, since 2018. Initially, the combination therapy showed a fair repigmentation response, but in the last 2 years didnâ€™t show significant improvement of repigmentation. According to cellular immune mechanisms, melanocyte destruction in vitiligo involves CD8 + T cells. Several theories of the occurrence of vitiligo in HIV patients are associated with a decrease in the ratio of CD4 + / CD8 + and autoantibodies to melanocytes. Management in this patient includes a combination therapy, but since there was minimum response, we gave additional therapy which was punch graft. Our patient had received two punch graft procedures on the skin of the neck. The first one was on February, 2020 and the second one was on October, 2020; both showed significant results. Â